The emergence of Clostridium thermocellum as a high utility candidate for consolidated bioprocessing applications - Akinosho, Hannah; Yee, Kelsey; Close, Dan; Ragauskas, Arthur (Frontiers in Chemistry, 2014)
First isolated in 1926, Clostridium thermocellum has recently received increased attention as a high utility candidate for use in consolidated bioprocessing applications. These applications, which seek to process lignocellulosic biomass directly into useful products such as ethanol, are gaining traction as economically feasible routes towards the production of fuel and other high value chemical compounds as the shortcomings of fossil fuels become evident. This review evaluates C. thermocellum’s role in this transitory process by highlighting recent discoveries relating to its genomic, transcriptomic, proteomic, and metabolomic responses to varying biomass sources, with a special emphasis placed on providing an overview of its unique, multivariate enzyme cellulosome complex and the role that this structure performs during biomass degradation. Both naturally evolved and genetically engineered strains are examined in light of their unique attributes and responses to various biomass treatment conditions, and the genetic tools that have been employed for their creation are presented. Several future routes for potential industrial usage are presented, and it is concluded that, although there have been many advances to significantly improve C. thermocellum’s amenability to industrial use, several hurdles still remain to be overcome as this unique organism enjoys increased attention within the scientific community.